Impact of Controlled Heating and Cooling on Hardness, Impact and Structure of Sand-casted SAE 1040 Specimen - Mrs. A.Sunanda, Dr. M. V. Jagannadha Raju (International Journal of Advanced Science and Technology, 2020)
This paper focuses on the hardness, impact, and structural behavior of sand cast medium carbon steel components under controlled heating and cooling conditions. To find out the behavior of hardness and impact four types of heat treatment operations such as annealing, normalizing, quenching, tempering at different temperatures were performed on the specimens. The specimens were machined according to standards, later for hardness Rockwell hardness test and for impact Charpy impact test was conducted. For different heat treatment operations, different values of hardness and impact were observed after Rockwell and Charpy impact tests. Microstructure analysis was carried out using an optical microscope. From the results, there are significant variations in the microstructure and mechanical properties of the different heat-treated samples. Keywords:Hardness, Heat treatment, Impact, medium carbon steel, Microstructure, Sand cast.